Macro-economic models for planning and policy-making - United Nations (Geneva, United Nations, 1967)
This report consists of the material prepared for, and information derived from, the Fourth Meeting of Senior Economic Advisers to ECE Governments.
"United Nations publications. Sales no.: E.67.II.E.3."
oif 12/04/2019
Loans
Keywords: Economic policy--Mathematical models; Macroeconomics--Mathematical models